Reducing medication errors in hospital discharge summaries: a randomised controlled trial. Issue 1 (16th January 2017) - Tong, Erica Y; Roman, Cristina P; Mitra, Biswadev; Yip, Gary S; Gibbs, Harry; Newnham, Harvey H; Smit, De Villiers; Galbraith, Kirsten; Dooley, Michael J
Abstract: Objectives: To evaluate whether pharmacists completing the medication management plan in the medical discharge summary reduced the rate of medication errors in these summaries. Design: Unblinded, cluster randomised, controlled investigation of medication management plans for patients discharged after an inpatient stay in a general medical unit. Setting: The Alfred Hospital, an adult major referral hospital in metropolitan Melbourne, with an annual emergency department attendance of about 60000 patients. Participants: The evaluation included patients' discharge summaries for the period 16 March 2015 – 27 July 2015. Interventions: Patients randomised to the intervention arm received medication management plans completed by a pharmacist (intervention); those in the control arm received standard medical discharge summaries (control). Main outcome measures: The primary outcome variable was a discharge summary including a medication error identified by an independent assessor. Results: At least one medication error was identified in the summaries of 265 of 431 patients (61.5%) in the control arm, compared with 60 of 401 patients (15%) in the intervention arm ( P <0.01). The absolute risk reduction was 46.5% (95% CI, 40.7–52.3%); the number needed to treat (NNT) to avoid one error was 2.2 (95% CI, 1.9–2.5). The absolute risk reduction for a high or extreme risk error was 9.6% (95% CI, 6.4–12.8%), with an NNT of 10.4 (95% CI, 7.8–15.5). Conclusions: Pharmacists completing medication management plans in the discharge summary significantly reduced the rate of medication errors (including errors of high and extreme risk) in medication summaries for general medical patients. Australia New Zealand Clinical Trials Registry number: ACTRN12616001034426.